Testing the Effects of Modality and Narration Style on Patients' Information Use in a Lung Cancer Treatment Decision Aid. (November 2020) - Yılmaz, Nida Gizem; Van Weert, Julia C. M.; Peters, Ellen; Lissenberg-Witte, Birgit I.; Becker, Annemarie; Senan, Suresh; Dickhoff, Chris; Timmermans, Daniëlle R. M.; Damman, Olga C.
Background: Risk information in patient decision aids (PDAs) is often difficult for older patients to process. Providing audiovisual and narrative information may enhance the understanding and use of health-related information. We studied the effects on patients' information processing and use of audiovisual and narrative information of an early-stage non–small-cell lung cancer treatment decision aid explaining surgery and stereotactic ablative radiotherapy. We further investigated differences between older and younger patients. Methods: We conducted a 2 (modality: textual v. audiovisual) × 2 (narration style: factual v. narrative) online experiment among cancer patients and survivors ( N = 305; Mage = 62.42, SD = 11.68 y). Age was included as a potential modifier: younger (<65 y) versus older (≥65 y) age. We assessed 1) perceived cognitive load, 2) satisfaction with information, 3) comprehension, 4) information recall, and 5) decisional conflict. Analysis of variance was used for data analysis. Results: Irrespective of patient age, audiovisual information (compared with textual information) led to lower perceived cognitive load, higher satisfaction with information, and lower decisional conflict (subscale Effective Decision). Narrative information (compared with factual information) led to reduced decisional conflict (subscale Uncertainty) but only in younger patients. Combining audiovisual information with factual information also resulted in lower perceived cognitive load in younger patients as compared with older patients. Limitations: Patients who actually face the decision, especially older patients, might be more motivated to process our decision-aid information than the present study participants who responded to a hypothetical situation online. Conclusions: Providing participants with audiovisual information, irrespective of their age, improved their processing and use of information in a decision aid. Narratives did not clearly benefit information processing.